2004
DOI: 10.1136/vr.155.3.83
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in the diagnosis and surgical management of sacral osteochondrosis in a mastiff dog

Abstract: The clinical, radiographic, magnetic resonance imaging (MRI), surgical and pathological findings related to an osteochondral lesion of the sacrum in a mastiff dog are described. The dog showed chronic signs of pain in its pelvic limbs. Radiography revealed a triangular mineralised opacity at the craniodorsal aspect of the sacrum consistent with sacral osteochondrosis. A T2-weighted spin-echo MRI revealed dorsal and lateral compression of the cauda equina. The osteochondral fragment was removed via a dorsal lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Surgical options for the treatment of sacral osteochondrosis are combinations of dorsal laminectomy and removal of the osteochondrosis fragment, with or without disc fenestration, and distraction and fusion of the lumbosacral joint 5,8 . Hanna suggests that fixation is only required when joint instability is evident preoperatively 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical options for the treatment of sacral osteochondrosis are combinations of dorsal laminectomy and removal of the osteochondrosis fragment, with or without disc fenestration, and distraction and fusion of the lumbosacral joint 5,8 . Hanna suggests that fixation is only required when joint instability is evident preoperatively 5 .…”
Section: Discussionmentioning
confidence: 99%
“…8 The described age of onset for clinical and asymptomatic cases ranges from 9 months to 13 years of age. 3,5,6,9 In the case described herein, the dog had clinical signs that may have developed as early as 2 months of age. Although it is unclear if these signs were due to sacral OC.…”
Section: Discussionmentioning
confidence: 85%
“…Magnetic resonance imaging (MRI) and CT are often used to further define the size of the lesions and the amount of nerve root compression. 9,10 In this case, MRI was deemed unnecessary, the diagnosis being clear on CT only. The ventral displacement of the sacrum relative to the vertebral body of L7 occasionally present in dogs with degenerative LS stenosis (DLSS) has been proposed as evidence of instability of the LSJ [11][12][13] which matches our conclusions in this case.…”
Section: Discussionmentioning
confidence: 93%
“…Lumbosacral OCD has been described in 68 German Shepherds, 4 Boxers, 3 Rottweilers, 2 Great Danes, 2 Springer spaniels, 2 Mastiff dogs, a Newfoundland dog and a Bernese mountain dog. (Lang et al, 1992;Snaps et al, 1998;Kriegleder, 2000;Hanna, 2001;Glyde et al, 2004;Michal et al, 2004;Mathis et al, 2009). To the authors' knowledge this is the first case reported in a Beagle.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, osteochondrosis of the appendicular skeleton usually induces clinical signs early in life, during the developmental stages (Ekman and Carlson, 1998). This difference is probably due to the fact that the lumbosacral joint is not a synovial joint and the separation of an osteochondral fragment does not result in pain after the synovial fluid penetrates to the subchondral bone (Glyde et al, 2004). Generally, the sacral endplate is affected (Lang et al, 1992).…”
Section: Discussionmentioning
confidence: 99%